THE HISTORICAL AND SCIENTIFIC PATH OF UZBEK MEDICINE: FROM IBN SINA'S TREATISES TO DIGITAL HEALTHCARE - Khaytmatova Gulnoza Amanillaevna (Web of Journals Publishing, 2025)
This article explores the historical development of medicine in Uzbekistan, emphasizing the enduring influence of Ibn Sina (Avicenna) on modern medical practices. Avicenna’s seminal work, The Canon of Medicine, shaped medical theory for over six centuries and remains integral to contemporary healthcare. The article traces the evolution of medical thought from Avicenna’s holistic approach to the current advancements in Uzbekistan’s healthcare system, demonstrating the continuity of scientific progress. It highlights the intersections between medieval and modern clinical practices, including individualized treatment, evidence-based medicine, psychosomatics, pharmacology, and empirical methodologies. By examining the philosophical, clinical, and ethical parallels between Avicenna’s contributions and 21st-century medical standards, the article illustrates the profound legacy of Avicenna’s work in shaping both Eastern and Western medical traditions. Furthermore, it outlines Uzbekistan’s historical contributions to medicine and the challenges faced in the 20th and 21st centuries, culminating in the country’s healthcare reforms and advancements. The study underscores the relevance of Avicenna’s ideas in the context of contemporary medicine, emphasizing their role in the ongoing development of Uzbekistan’s healthcare system.
Keywords: History, Ibn Sina (Avicenna), The Canon of Medicine, Medical history, Uzbekistan, Medical ethics, Modern medicine, Interdisciplinary approach, Global scientific progress.